2021
DOI: 10.1093/milmed/usaa572
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Seasonal Influenza Vaccine Among U.S. Army Civilians and Dependents in the Kaiserslautern Military Community: A Mixed-Methods Survey

Abstract: Introduction Influenza is a globally occurring viral respiratory infection that can lead to hospitalizations and death. An influenza outbreak can interfere with combat readiness in a military setting, as the infection can incapacitate soldiers. Vaccination remains the most effective tool to prevent and mitigate seasonal influenza. Although influenza vaccinations for U.S. Army soldiers can be monitored through military health systems, those systems cannot capture DoD civilians and Army depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(15 reference statements)
1
2
1
Order By: Relevance
“…In line with previous evidence ( 28 , 29 ), vaccination history in former seasons is conducive to future seasons. This hints to administrative departments to take action before it is too late.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous evidence ( 28 , 29 ), vaccination history in former seasons is conducive to future seasons. This hints to administrative departments to take action before it is too late.…”
Section: Discussionsupporting
confidence: 91%
“…Similar studies in Greece before the COVID-19 pandemic showed a vaccination uptake of 56.6% for people over the age of 60 [ 40 ] and of 34.8% [ 41 ] to 37.9% [ 42 ] for high-risk populations. Moreover, vaccination intention rate against influenza for the 2020–2021 season among high-risk people in Spain, Ireland, Japan, and USA was much higher compared to that in our study ranging from 43.3% to 79.7% [ 13 , 14 , 15 , 16 ]. Moreover, such intention rate was higher in studies including patients in United Kingdom (76.3%) [ 43 ] and China (54%) [ 44 ] before the pandemic.…”
Section: Discussioncontrasting
confidence: 72%
“…During the COVID-19 pandemic, only four studies [ 13 , 14 , 15 , 16 ] assessed the intentions of high-risk populations to receive the influenza vaccine for the 2020–2021 season. Additionally, these studies investigated only demographic variables and previous influenza vaccine acceptance as potential predictors.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Before the COVID-19 pandemic, there was hesitancy to other vaccines, including polio, 6 measles, mumps and rubella (MMR), 7 and influenza. 8 In some cases, vaccine hesitancy was directly linked to actions of the medical establishment. For example, public concern for the poliovirus vaccination increased dramatically after the Cutter Incident of 1955, in which multiple children developed paralysis after being unintentionally administered a vaccine that contained live virus because of a laboratory processing error and contamination of cell debris which resulted in inadequate inactivation of the virus.…”
Section: Introductionmentioning
confidence: 99%